The implementation of variable costing in the management of profitability of sales in trade companies - Anna Dyhdalewicz (e-Finanse: Financial Internet Quarterly, 2015)
The aims of the paper are twofold: first, to present selected approaches to the construction of an income statement based on variable costing, which evolved towards the preparation of a tool for multidimensional measurement and an analysis of profitability of sales; second, to discuss the possibility of using it in trade companies. The paper is composed of the following parts: 1) The first part contains a presentation of the general rules of construction of financial result accounts on the basis of variable costing, providing the basis of preparing multi task contribution income statements in various entities; 2) The second part is devoted to the general assumptions concerning the activity in trade companies, which should be observed in the creation of the information needed for the segment profitability reporting according to the rules of variable costing; 3) In the third part, one proposes a report on customer profitability and basic financial ratios, which are related to it, are defined. The financial ratios can be used to conduct an analysis of profitability of sales in a trade company. This approach uses the evaluation of profitability made by taking into account the size and structure of sales and it includes the costs related to customer service. 4) In the last parts, the conclusions are made on the basis of the discussion presented in the paper. The methodology of the contribution income statement on the basis of variable costing enables its implementation in various branches of business, including trading activity, due to universal rules used for its creation. However, constructing a profitability report requires individual assumptions, which take into consideration the specific character of a given trade company and its information needs.
Keywords: M21; M41; 330; variable costi ng; contributi on margin; income statement; profi tability of sales; trade company